Does rectal diclofenac reduce post-ERCP pancreatitis? A district general hospital experience. Issue 1 (10th August 2017) - Sheiybani, Giovanna; Brydon, Peter; Toolan, Miriam; Linehan, John; Farrant, Mark; Colleypriest, Benjamin
Abstract : Introduction: There is controversy in the literature recently regarding the efficacy of rectal non-steroidal anti-inflammatory drugs (NSAID) to prevent post-ERCP pancreatitis (PEP). The aim of this study was to compare the incidence of PEP in three distinct groups of patients at the Royal United Hospital, Bath: no use of rectal diclofenac, selective use and blanket use without contraindication. Method: Readmission data, blood results, radiology reports and discharge summaries were used to identify patients with PEP from August 2010 to December 2015. The administration of rectal diclofenac postprocedure was recorded from the endoscopy reporting system. Results: 1318 endoscopic retrograde cholangiopancreatographies (ERCP) were performed by four endoscopists during the study period with 66 (5.0%) cases of pancreatitis. 445 ERCPs were performed prior to the introduction of NSAID use during which time, with an incidence of 35 (7.9%) episodes of PEP. During the selective period of NSAID use (high-risk patients) 539 ERCPs were performed and 72 (13.4%) patients received NSAIDs. 17 (3.2%) developed PEP. 334 ERCPs were performed when NSAIDs were given to all patients without contraindication. 289 (86.5%) of patients received rectal diclofenac and 13 (3.9%) developed pancreatitis. There is a statistically significant decrease in PEP comparing the groups of patients receiving NSAIDs selectively (p=0.0009) or routinely (p=0.0172) when compared with none. There is no difference between the selective and routine group (p=0.571). Conclusion: Our data demonstrate that the introduction of a selective or routine use of NSAIDs for PEP in a District General Hospital (DGH) significantly decreases the risk of pancreatitis (risk reduction 43.7%).